Potensi Pengemas Ramah Lingkungan Untuk Mempertahankan Mutu Dan Keamanan Pangan - Budi Hartoyo (Jurnal Agrifoodtech, 2023)
Food ingredients in general are very sensitive and easily experience quality degradation due to environmental, chemical, biochemical, microbiological, oxygen, water, light and temperature factors. To prevent this damage, the food product is packaged with plastic packaging material. Until now, plastic polymers are the most widely used packaging materials. In Indonesia, the use of plastic packaging materials by the food industry and other food business actors as food packaging has occupied a portion of 80% and 55%. This will of course result in danger to the environment. Packaging with edible coating/film is a relatively new food preservation technique. Research on coating food products with edible coating/film has been widely carried out and has been proven to extend the shelf life and improve the quality of food products. The safest, most potential and most widely researched polymer material for edible coating/film is a renewable organic material based on starch. Starch is a type of polysaccharide from plants that is abundantly available in nature, is biodegradable, easy to obtain and cheap. Edible packaging made from organic materials has the opportunity to be developed to meet the needs of safe packaging for consumers and support sustainable agriculture and realize the Sustainable Development Goals (SDG's), considering that there is an abundance of edible packaging materials in Indonesia that have not been utilized optimally. The application of environmentally friendly edible packaging is expected to provide very significant benefits in the development of food technology, namely aspects of maintaining quality, both in terms of nutritional value and food safety, extending product shelf life and being able to increase the added value of the materials that make up edible packaging.